USE OF INNOVATIVE TECHNOLOGIES FOR ENHANCED TEACHING AND TRAINING IN THE TECHNOLOGY SERVICE SECTION - Abdullaeva Feruza; Yusupova Dinara (American Journals Publishing, 2023)
The Department of Service Technology plays a crucial role in preparing students for the fast-growing landscape of technological advancement. When educational institutions seek to provide relevant education in the field, integration of innovative technologies in teaching becomes necessary. This article provides recommendations on the use of modern technologies in the technology service section, their potential benefits, problems and successful implementation.
Keywords: Education, computer, information and virtual technology, interactive, distance learning.